Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan Central Electric Melalui Kepuasan Kerja - Hadisutrisno Hadisutrisno; Mochammad Subhaan (STIKes Ibnu Sina Ajibarang, 2024)
Today's business competition is increasingly fierce, requiring an organization to have high competitive advantage. In order to obtain the expected quality of performance, the company pays great attention to the sense of job satisfaction of its employees. The sampling method used in this research is the saturated sample method, namely where the total population of Centra Electric employees is 63 people. Descriptive analysis in this research is in the form of respondents' responses to the statements submitted in the questionnaire in the form of frequency, percent, valid percentage and cumulative percentage. This research states that the Motivation variable has a P-Value value of 0.020 < 0.05, and a statistical t value of 2.333 > 1.96 and work compensation has a P-Value value of 0.000 < 0.05, and a statistical t value of 8.446 > 1.96 has an effect on satisfaction. Employee Work. The work motivation variable has a P-value of 0.006 < 0.05, and the statistical t value is 2.778 > 1.96. And the job satisfaction variable has an effect on performance. Partially, job satisfaction has a significant positive effect on employee performance. Meanwhile, the Compensation variable has no effect on Employee Job Satisfaction at Central Electric Semarang City. The research results show that the P-Value value is 0.375>0.05, and the statistical t value is 0.888<1.96. Although compensation can be a significant factor in employee motivation and job satisfaction, there are situations where compensation may not directly impact performance. In conclusion, from the results of this research, non-financial factors can become more dominant in motivating employees. Compensation variables influence employee performance at Central Electric, Semarang City, which is partially mediated by Job Satisfaction.